The Presence of Privation in Dana Gioia's "Homecoming" - Hren, Joshua (Christianity & literature, 2025)
In The City of God St. Augustine argues that “evil has no positive nature; what we call evil is merely the lack of something that is good.” Still, if evil has no positive nature, its very absence seems to become a presence each time an evil deed is done, a phenomenon Dana Gioia incarnates in his long narrative poem “Homecoming.” This essay relies on St. Augustine and Nietzsche to articulate the nature of evil in Gioia’s “Homecoming,” wherein evil is no mere lack of niceness, no simple “mistake” or “error,” but a deliberate and ambitious rebellion against God.